89/5000 Ion-state chloride penetration profiles in concretes in the A / C range 045 to 0.65 - Chávez Machado, Jesús Angel (2003)
The objective of the work carried out is to continue research on the effect of chloride ions on the variables that determine the behavior of concrete as a protective covering for reinforcing steel, when it is subjected to the environmental conditions of the marine coast of the Peruvian coast. Considering the relevance of the water / cement ratio in obtaining the compact properties of concrete and therefore in the ease with which chlorides can diffuse in this medium, we proceeded to prepare aggregates from the region with groundwater and Type I Portland cement, forty-five 75 x 150 mm cylindrical specimens, which after undergoing 1, 3 and 7 days of curing were paraffin-watered on all sides except in a basal plane and then immersed in water tridistilled with sodium chloride of high purity degree, in proportions similar to the salinity conditions of the Pacific Ocean in the Peruvian coast. After 30 days, the specimens were removed, then dust samples were extracted on the vertical axis every 0.02 m deep, using mechanical methods, obtaining 315 samples that were analyzed using a digital selective ion analyzer. Selective ion tests for chlorides, after immersing the concrete specimens in artificial seawater for 30 days, revealed that the concentration of chloride / sample weight varies with the depth of penetration according to the concentration profiles found. , following the typical trend of the diffusion of chlorides in concrete. The higher the water / cement ratio, the values ​​of the chloride concentration for a given penetration depth are generally greater. The values ​​of the surface concentrations of chlorides increase as the water / cement ratio increases.